"Personal mission statement": an analysis of medical students' and general practitioners' reflections on personal beliefs, values and goals in life - Chew, Boon How; Lee, Ping Yein; Ismail, Irmi Zarina (Academy of Family Physicians of Malaysia, 2014)
Background: Personal mission in life can determine the motivation, happiness, career advancement and fulfilment in life of the medical students (MSs) along with improvement in professional/clinical performance of the family physicians. This study explored the personal beliefs, values and goals in the lives of MSs and general practitioners (GPs). Methods: Fourth-year MSs at the Universiti Putra Malaysia and GPs who participated in a 2-hour session on ‘Ethics in Family Medicine’ in 2012 were invited. All the participants submitted the post-session written reflections about their personal missions in life. The written reflections were analysed using thematic analysis. Results: A total of 87 MSs and 31 GPs submitted their written reflections. The authors identified 17 categories from the reflections contained by four themes-good vs. smart doctor, professional improvement vs. self-improvement, self-fulfilment and expressed motivation. The most common categories were “to be a good doctor” (97/330) and “professional improvement” (65/330). Many MSs had expressed motivation and wanted to be a smart doctor as compared to the GPs, whereas a larger number of GPs wished to have a fulfilled life and be a good doctor through professional improvement. Conclusion: The difference between the two student groups might indicate different levels of maturity and life experiences. Medical teachers should engage students more effectively in orientating them towards the essential values needed in medical practice.